2001
DOI: 10.5032/jae.2001.02046
|View full text |Cite
|
Sign up to set email alerts
|

Factors Identified When Selecting A Major In Agriculture

Abstract: Student recruitment has a vital role in successful colleges of agriculture. The study investigated factors that influence students' decision to select a major within available agricultural disciplines. The population was full-time college students majoring in an agricultural discipline. The results provide a demographic profile of students, data on their perceived sources of influence and considerations when selecting an agriculture major. One factor, prior experience in agriculture, was identified as the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 0 publications
4
43
0
Order By: Relevance
“…Our participants agreed and felt that agriculture colleges need to send more positive signals to parents in terms of the career prospects for their children. Wildman and Torres (2001) found that previous experience in agriculture was the determining factor in why college students enrolled in agriculture programs. Our participants felt that this experience with agricultural education at the high school level is critical, but is being pushed aside due to the demands of work, sports, and other activities that preclude participation in agriculture programs.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our participants agreed and felt that agriculture colleges need to send more positive signals to parents in terms of the career prospects for their children. Wildman and Torres (2001) found that previous experience in agriculture was the determining factor in why college students enrolled in agriculture programs. Our participants felt that this experience with agricultural education at the high school level is critical, but is being pushed aside due to the demands of work, sports, and other activities that preclude participation in agriculture programs.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Various studies have examined whether secondary agriculture students intend to pursue teaching in agriculture as a career (Lawver & Torres, 2012), what expert secondary agricultural education teachers perceive to be the problems in recruiting secondary students into teaching (Dyer & Breja, 2003), the characteristics that determine students' decisions to choose agricultural education as a career (Park & Rudd, 2005), factors that influence students' decisions to pursue agricultural education as a career (Reis & Kahler, 1997), and the factors that influence which area of agricultural science to study as a major in college (Wildman & Torres, 2001). However, after these periodic examinations, we…”
mentioning
confidence: 99%
“…The project's research team identified questionnaire items used in previous studies with similar purposes (Cecchettini, Sommer, & Leising, 1992;Dyer, Breja, & Andreasen, 1999;Dyer, Lacey, & Osborne, 1996;Faulkner, Baggett, Bowen, & Bowen, 2009;Wildman & Torres, 2001) The questionnaire was field-tested with a similar population of students from a different high school and found to be reliable ( = .70).…”
Section: Hsai Questionnairementioning
confidence: 99%
“…Research and writing within agricultural education indicates the secondary agriculture teacher positively influences their students' career decisions in general (Esters & Bowen, 2005;Fraze, Wingenbach, Rutherford, & Wolfskill, 2011;Priest, Ricketts, Navarro, & Duncan, 2009;Marx, Simonsen, & Kitchel, 2014;Wildman & Torres, 2001), but more important to the present study, students' decisions to pursue teaching (Ball & Torres, 2010;Lawver & Torres, 2012;Park & Rudd, 2005). According Wildman and Torres (2001), top influences on students' choice of an agriculturally related college major included prior experience in agriculture, other agricultural experiences, agriculture and extension professionals, and perceptions of the academic department.…”
Section: Review Of Literaturementioning
confidence: 99%
“…According Wildman and Torres (2001), top influences on students' choice of an agriculturally related college major included prior experience in agriculture, other agricultural experiences, agriculture and extension professionals, and perceptions of the academic department. Individual aspects of the SBAE program do not seem to influence the decision to choose teaching as a career according to Lawver and Torres (2011).…”
Section: Review Of Literaturementioning
confidence: 99%